Market integration through data protection : an analysis of the Insurance and Financial Industries in the EU - Viola de Azevedo Cunha, Mario (Law, Governance and Technology Series, 2013)
In the context of the continuous advance of information technologies and biomedicine, and of the creation of economic blocs, this work analyzes the role that data protection plays in the integration of markets. It puts special emphasis on financial and insurance services.  Further, it identifies the differences in the data protection systems of EU member states and provides some recommendations for the upcoming review of the EU Data Protection Framework. Divided into four parts, the book starts out with a discussion of the evolution of the right to privacy, focusing on the last few decades, and taking into account the development of new technologies.  The second part discusses the interaction between data protection and specific industries that serve as case studies: insurance, banking and credit reporting. The focus of this part is on generalization and discrimination, adverse selection and the processing of sensitive and genetic data. The third part of the book presents an analysis of the legislation of three EU Member States (France, Italy and UK). Specific elements of analysis that are compared are the concepts of personal and anonymous data, data protection principles, the role of the data protection authorities, the role of the data protection officer, data subjects' rights, the processing of sensitive data, the processing of genetic data and the experience of the case studies in processing data. The book concludes by proposing recommendations aiming at increasing the level of harmonisation at the EU level and at fostering the creation of a single market for the industries which use personal information as an important raw material for their activities, taking into account the different levels of data protection that exist in EU member states.